Konflik dan Resolusi: Studi pada Pemilihan Umum Kabupaten Aceh Utara Tahun 2019 - Hardiansyah; Suadi; Abidin (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2021)
This article aims to provide a descriptive description of the conflict in the counting and recapitulation of the 2019 general election in the North Aceh Regency. This study uses qualitative methods, data obtained from observations, interviews, and relevant documents or literature. Research informants consist of elements of election organizers, election contestants, and stakeholders. This study found that the conflict was motivated by unintentional factors related to competence, workload, and weaknesses in supporting facilities for the implementation of elections, as well as factors related to the transparency of election administrators. Furthermore, the conflicting parties seek to find conflict resolution through mediation and adjudication.